(untitled) (Journal of Educational Sciences, 2025)
This study examines the potential risks and problems arising in the integration of artificial intelligence (AI) technologies into the system of higher education from the position of the teaching staff of Kazakhstani universities. Against the background of rapid development of AI and its active implementation in various spheres, special attention is paid to its impact on the transformation of the educational process. The main purpose of the work is to identify the peculiarities of teachers’ perception of AI, assess its impact on the quality of teaching and analyze the possible threats associated with the use of AI tools in the educational process. The main objective of the study is to comprehensively analyze the attitude of the teaching staff to the introduction of AI in the educational environment, as well as to determine its positive and negative aspects and identify the main difficulties and risks accompanying the use of these technologies. The methodological basis of the study is based on the application of both quantitative and qualitative methods of data collection. The sample included 180 teachers of higher education institutions working in three strategically important regions of the country - Astana, Almaty and Taldykorgan. Various parameters were taken into account when forming the sample, including disciplinary affiliation (humanities, technical and creative fields), type of institution (national, public and private) and academic status of the participants (professors, associate professors, senior lecturers and young specialists). Preliminary analysis showed that 60% of respondents already use AI tools (e.g., ChatGPT, Grammarly, QuillBot) in their professional activities, 30% are familiar with the technologies but do not use them yet, and 10% are skeptical about their implementation. Key words: artificial intelligence, higher education, students, digital competence, academic integrity, innovative technologies, information technology.